Proceedings of the 9th Nordic Conference on Human-Computer Interaction 2016
DOI: 10.1145/2971485.2971494
|View full text |Cite
|
Sign up to set email alerts
|

Informing Design for Reflection

Abstract: There is an increasing interest in HCI in designing to support reflection in users. In this paper, we specifically focus on everyday life reflection, covering and connecting a broad range of topics from someone's life rather than focusing on a very specific aspect. Although many systems aim to support reflection, few are based on an overview of how people currently integrate reflection in everyday life. In this paper, we aim to contribute to this gap through a questionnaire on everyday life reflection practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Similar to the findings of Mols et al on everyday reflection [39], some participants explained that "I keep just thinking about things, just randomly they keep popping into my head.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to the findings of Mols et al on everyday reflection [39], some participants explained that "I keep just thinking about things, just randomly they keep popping into my head.…”
Section: Resultssupporting
confidence: 72%
“…While a sizable body of work has emerged around the importance of reflection in the design process [3,42], there has been increasing focus within HCI on the reflective experiences of 'everyday' technology users [3,39,40]. Yet many questions remain on how best to facilitate reflective experiences through interaction design [3,19,44], which partly stems from the lack of a common understanding of what reflection in HCI entails [4,19].…”
Section: Related Workmentioning
confidence: 99%
“…A systematic review of 700+ papers [65] recommended the Reflection Questionnaire [44] and Self-Reflection and Insight Scale (SRIS) [32] as most rigorous. The SRIS has informed HCI design considerations for supporting everyday reflection [60], but is not technology focused, instead quantifying people's tendency to self-reflect through three factors: insight (people's ability to understand themselves), engagement in self-reflection (frequency at which people self-reflect) and need for reflection (people's motivation to reflect). It was tested with a confirmatory factor analysis, test-retest study, and a comparison between Psychology students who did and did not keep a diary.…”
Section: Measuring Reflectionmentioning
confidence: 99%
“…Our findings also emphasize the importance of selective retrieval of positive memories, an aspect less recognized in HCI memory work. Previous findings have shown that retrieving positive memories can be problematic for depressed clients [13,15] who at the time of retrieval are experiencing negative moods, as it can trigger rumination [41], and comparison with one's past thus worsening the present negative mood [33].…”
Section: Positive Memory Banks For Active Encoding and Selective Retrmentioning
confidence: 99%